An Analytical Review on Emerging Future Network Technologies in Healthcare: Issues, Challenges and Prospects for the Future - Kumar, Narendar; Waqar, Abdul; Khan, Muhammad Salman; Salman, Muhammad (Universitas Indonesia, 2024)
This review research article covers in detail healthcare issues and problems related to emerging network technologies, including 5G, satellite communication, and body area networks. The main target is to provide readings that are preliminary so as to get a more rapid in-depth exploitation of this area through which the existing landscape can be figured out and related areas in which further research and probing can be done. This review focuses on core components such as security and privacy, transmission performance, regulatory issues, coexistence issues, and standardization, and explores the issues of securing patient data and confidentiality and measures of performance which play a critical role in healthcare application. Identifying key challenges and matured areas in the review, the review points out researchers to confirmed areas where more efforts are required, like robust security protocols, more innovative regulatory solutions, and new interoperability standards. In this way this study corroborates the need for continued innovation and research in healthcare network technologies that will ultimately result in an improved quality of healthcare delivery and, hence, an improved result for the patient